Phase-transfer catalysis for synthesis of ethyl 2-(4-nitrophenoxy)acetate under sonication- kinetic aspects - V. Rajendran; P. Abimannan (Iranian Journal of Chemical Engineering)
Ultrasound assisted phase-transfer catalyzed preparation of ethyl 2-(4-nitrophenoxy)acetate from the corresponding p-nitrophenol and ethyl 2-bromoacetate using the mild solid base, anhydrous potassium carbonate, under very mild conditions is reported. The solid-liquid reactions were performed in a batch reactor equipped with reflux condenser, and ultrasonic irradiations were introduced using an ultrasonic bath operating at a frequency of 28 kHz with a power rating of 300 W. The reaction was carried out at 50°C under pseudo-first order conditions and was monitored by gas chromatography (GC). From the experimental data, a rate expression had been developed to explain the kinetic behavior of the reaction from which the apparent rate constant (kapp) of the organic phase was attained. The effects of different operating parameters such as stirring rate, temperature, catalyst loading and kind of Phase-transfer catalysts, base variation and quantity of water, kind of solvents have been investigated to maximize the yield of synthesis of ethyl 2-(4-nitrophenoxy)acetate.